2007
DOI: 10.1038/ncponc0719
|View full text |Cite
|
Sign up to set email alerts
|

Medulloblastoma, acute myelocytic leukemia and colonic carcinomas in a child with biallelic MSH6 mutations

Abstract: Background A 13-year-old girl presented with rectal bleeding and was found to have two colonic carcinomas (stage Dukes' C) and multiple colonic polyps. At the age of 7 years she had widespread hyperpigmented and hypopigmented skin lesions, and had developed medulloblastoma, which was treated with chemotherapy and craniospinal irradiation. At the age of 10 years she had developed acute myelocytic leukemia, M5. She was treated with chemotherapy including sibling bone marrow transplant with busulfan/cyclophospham… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
78
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(81 citation statements)
references
References 16 publications
3
78
0
Order By: Relevance
“…32 Recently, the terms 'CoLoN' (for Colon tumours and/or leukaemia/lymphoma and/or neurofibromatosis features), 34 and 'mismatch repair deficiency syndrome (MMR-D)' have been suggested. 28 Hereby, we provide evidence for CCS in six children from two consanguineous families carrying homozygous PMS2 germline mutations. Five of them were affected by earlyonset malignancies from the tumour spectrum reported so far in biallelic MMR germline mutation carriers, and presented with multiple CALS.…”
Section: Introductionmentioning
confidence: 99%
“…32 Recently, the terms 'CoLoN' (for Colon tumours and/or leukaemia/lymphoma and/or neurofibromatosis features), 34 and 'mismatch repair deficiency syndrome (MMR-D)' have been suggested. 28 Hereby, we provide evidence for CCS in six children from two consanguineous families carrying homozygous PMS2 germline mutations. Five of them were affected by earlyonset malignancies from the tumour spectrum reported so far in biallelic MMR germline mutation carriers, and presented with multiple CALS.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14][15] However, signs reminiscent of neurofibromatosis type 1 (NF1), in particular café-aulait macules (CALMs), are much more common and were observed in the majority of the reported cases (63/92). There are only 2 patients explicitly reported to lack CALMs or other signs of NF1.…”
mentioning
confidence: 99%
“…Péron et al 2 have shown in 3 CMMR-D patients that 15,19,20 . It remains to be seen whether defective IgA and IgG production is a common feature of CMMR-D. Fortunately, severe bacterial infections have not been reported to occur at high frequencies in persons with CMMR-D.…”
mentioning
confidence: 99%
“…Mismatch repair deficiencies have been associated with paediatric brain tumours in a hereditary context. Case reports have described MMR germline mutations combined with NF1-like clinical features in children presenting medulloblastoma or high-grade glioma, described as a "mismatch repair-deficiency (MMR-D) syndrome" (summary in Table 5) (Agostini et al, 2005;De Rosa et al, 2000;Giunti et al, 2009;Hegde et al, 2005;Kruger et al, 2008;Menko et al, 2004;Ostergaard et al, 2005;Poley et al, 2007;Roy et al, 2009;Scott et al, 2007;Toledano et al, 2009;Viana-Pereira et al, submitted;Wagner et al, 2003;Wang et al, 1999). Also in our study there was a MSI-H paediatric high-grade glioma with clinical characteristics of NF1 (multiple café-au-lait spots).…”
Section: Microsatellite Instabilitymentioning
confidence: 99%